Congenital Giant Dysplastic Kidney Presenting as Respiratory Distress: A Case Report - Mahesh Kumar; Geeta Gathwala; KN Rattan; Sandeep Lather; Poonam Dalal (EL-Med-Pub, 2016)
Multicystic dysplastic kidney (MCDK) is the most common form of renal cystic disease in children and is one of the most common causes of abdominal mass in infancy. Here in we are reporting a rare case of a large MCKD that caused respiratory compromise and the infant presented with respiratory distress.